MEMPERKUAT LITERASI DAN NUMERASI: KUNCI MEMBANGUN KUALITAS PENDIDIKAN DALAM IMPLEMENTASI KURIKULUM MERDEKA - Elsa Sari Mulyati; Sarah Nur Azzahra; Ichsan Fauzi Rachman (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research was motivated by the low literacy and numeracy problems in Indonesia. Many factors influence the weak level of literacy and numeracy among the community, especially students in Indonesia, one of which is the low interest in reading and learning culture in the community. This study aims to determine the various problems faced in the implementation of the independent curriculum and how strategies and efforts to improve literacy and numeracy in the implementation of the independent curriculum. The research method used is literature review by collecting and analyzing various sources in journals and articles from mass media. The results of the study stated that by strengthening literacy and numeracy can build quality education through the implementation of an independent curriculum.